Growth Opportunity, Ukuran Perusahaan dan Tingkat Utang Perusahaan dalam Perspektif Signaling Theory - Rahmat Setiawan (STIE AMKOP, 2022)
Companies with high growth opportunities have a high level of information asymmetry, so they need a positive signal delivered to financial markets to reduce the level of information asymmetry they have. Based on the Signaling Theory, an increase in corporate debt can be a positive signal about the company's performance in the future. The company is only willing to increase its debt when the company believes that the company's future performance is good. Therefore, an increase in corporate debt can be read as a valid positive signal that the company's future performance is good. In the perspective of Signaling Theory, companies with high growth opportunities will tend to have high levels of debt because companies with high growth opportunities have a high level of information asymmetry so they tend to use high levels of debt to reduce their level of information asymmetry and to realize investment projects with positive NPV. Therefore, in the perspective of Signaling Theory, growth opportunity has a positive effect on the level of corporate debt. The size of the influence of growth opportunity on the level of debt is influenced by the size of the company. Large companies have a low level of information asymmetry, so they do not need a positive signal to reduce information asymmetry. Therefore, in the perspective of Signaling Theory, the positive effect of growth opportunity on debt levels is weaker for large companies than for small companies. Keywords: Growth Opportunity, Company Size, Debt Level, Signaling Theory